CO2 Hydrogenation Induced by Mechanochemical Activation of Olivine With Water Under CO2 Atmosphere - Farina, Valeria; Gamba, Nadia S.; Gennari, Fabiana; Garroni, Sebastiano; Torre, Francesco; Taras, Alessandro; Enzo, Stefano; Mulas, Gabriele (Frontiers in Energy Research, 2019)
A study on the mechanochemical activation of the olivine in presence of H2O and under CO2 atmosphere have been approached, focusing both on the structural nature of the transformation and the conversion of CO2 to methane and light hydrocarbons. The mechanochemical process was carried out by high energy laboratory mills, with milling vials properly modified in order to be used as batch reactors. Chemical reactivity and reaction rates were investigated under different experimental conditions, evidencing increased performance with respect to the thermally activated process reported in literature. Mechanical treatment induced H2O and olivine activation, with consequent release of molecular H2 which, in turn, allowed hydrogenation of activated CO2. This last reaction also led, through a competitive process, to the precipitation of carbonate phases, whose composition and structural features were dependent of the CO2/H2O ratio.